Autoantibodies against the β(3)-Adrenoceptor Protect from Cardiac Dysfunction in a Rat Model of Pressure Overload - Wang, Jin (Public Library of Science, 2013)
β(3)-adrenoceptors (β(3)-ARs) mediate a negative inotropic effect in human ventricular cardiomyocytes, which is opposite to that of β(1)- and β(2)-ARs. It has been previously demonstrated that autoantibodies against the β(1/)β(2)-AR exist in the sera of some patients with heart failure (HF) and these autoantibodies display agonist-like effects. Our aim in this study was to observe whether autoantibodies against the β(3)-AR (β(3)-AR Abs) exist in the sera of patients with HF and to assess the effects of β(3)-AR Abs on rat model of pressure overload cardiomyopthy. In the present study, the level of β(3)-AR Abs in the sera of HF patients was screened by ELISA. β(3)-AR Abs from HF patients were administrated to male adult rats with abdominal aortic banding (AAB), and the cardiac function was measured by echocardiographic examination and hemodynamic studies. The biological effects of this autoantibody on cardiomyocytes were evaluated using a motion-edge detection system, intracellular calcium transient assay, and patch clamp techniques. Compared to healthy subjects, the frequency of occurrence and titer of β(3)-AR Abs in the sera of HF patients were greatly increased, and β(3)-AR Abs could prevent LV dilation and improve the cardiac function of rats with AAB. β(3)-AR Abs exhibited negative chronotropic and inotropic effects and were accompanied by a decreased intracellular Ca(2+) transient and membrane L-type Ca(2+) current in cardiomyocytes. Our results demonstrated the existence of β(3)-AR Abs in the sera of patients with HF and found that this autoantibody could alleviate the cardiac dysfunction induced by pressure-overload in AAB rats.